Auxotrophs of Plasmodium falciparum dependent on p-aminobenzoic acid for growth. - McConkey, G A (1994)
The isolation of auxotrophic strains of a parasite offers new opportunities for studying parasitology. We have isolated cloned lines of Plasmodium falciparum that, unlike the parent line from which they were derived, rely on exogenous p-aminobenzoic acid (PABA) for growth. Isolation involved random mutagenesis of a cloned line of P. falciparum and subsequent selection of PABA-dependent parasites. Both parent and PABA-dependent clones were analyzed for PABA uptake and synthesis. Each clone takes up comparable amounts of PABA from the medium. The parent line, clone 3D7, can synthesize PABA de novo, whereas the PABA-dependent clones cannot. The requirement of exogenous PABA for growth by the auxotrophic strains coupled with their inability to synthesize PABA indicates that normal parasite growth can be completely supported by either synthesis or salvage. This work further clarifies the relationship between the availability of PABA and success of the parasite, an issue of debate from classic studies showing reduced parasite load in individuals on milk-fed diets.